The famous five : Five have plenty of fun - Blyton, Enid; Eileen Alice Soper (illustrator) (London, Hodder Children's, 1997)
George is very cross when a spoilt American girl arrives at Kirrin Cottage in the middle of the night - dressed in disguise. But this is no time for George to be jealous - Berta is hiding from kidnappers and only the Famous Five can protect her.